Effortful Control and Extensive Observations of Negative Emotion as Joint Predictors of Teacher–Student Conflict in Childhood. Issue 1 (2nd January 2022) - Hernández, Maciel M.; Eisenberg, Nancy; Valiente, Carlos; Spinrad, Tracy L.; Johns, Sarah K.; Berger, Rebecca H.; Diaz, Anjolii; Silva, Kassondra M.; Thompson, Marilyn S.; Gal-Szabo, Diana E.; Southworth, Jody
ABSTRACT: Studies with extensive observations of real-life emotions at school are rare but might be especially useful for predicting school-related outcomes. This study evaluated observations of negative emotion expressivity in lunch and recreation settings across kindergarten, first grade, and second grade ( N = 301), kindergarten teachers' reports of children's effortful control, and kindergarten and second grade teachers' reports of their perceived conflict with children. In latent growth curve analyses, we tested whether individual trajectories of negative expressivity from kindergarten to second grade, based on estimated slopes, predicted teacher–student conflict in second grade, and whether effortful control in kindergarten moderated this association. Research findings : Negative expressivity levels in kindergarten significantly predicted higher levels of teacher–student conflict in second grade, controlling prior teacher–student conflict. Furthermore, greater increases in negative expressivity from kindergarten to second grade were associated with higher teacher–student conflict in second grade especially for children who had difficulties with effortful control in kindergarten. Practice or Policy : Results from this study have the potential to inform programs focused on reducing teacher–student conflict. The findings highlight the possibility of targeting both effortful control and negative emotion in the early elementary school transition as a means to improve teacher–student relationships.